Bibliometric Analysis of Rural Tourism and Sustainable Development Goals - Maria Elerina Douk Tunti; Falikhatun Falikhatun (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This paper aims to investigate the trends of rural tourism and sustainable development goals researchs through reviewing related scientific publications. Data were collected using the Publish or Perish (PoP) and SINTA databases. A Bibliometric analysis was conducted using the VOSViewer and Microsoft Excel software by utilizing information from the retrieved database. Further, data was encoded and analyzed through descriptive statistics and structural analysis. The results reveal that there is a rise of research papers that deal with rural tourism and sustainable development goals in the Asia region, where a significant portion of the published works was contributed from Indonesia and the common themes that emerged were among nature-based tourism, community-based tourism, bay tourism, agriculture and plantations, and local wisdom. Considering the criticality of the sustainable development concept in the contemporary context of rural tourism, more studies should delve into merging and investigating the relationship between the two themes.